Evaluasi Kebijakan Penganggaran Berbasis Kinerja di Pemerintah Daerah - Salwa Aidilla Fitri; Reva Siti Nasywa Simatupang; Nanda Mauliza; Mariana Mariana (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This study aims to analyze the implementation of performance-based budgeting in improving local government performance. The focus of the study is on the four main pillars in the implementation of performance-based budgeting, namely planning, implementation, reporting, and evaluation. This approach prioritizes effectiveness, efficiency, and accountability in budget management, as well as optimizing public resources to achieve measurable results and in accordance with national priorities. Through a literature review, this study identifies factors that influence budgeting performance in the local government sector, and explores the challenges faced in implementing a performance-based budgeting system, especially related to the efficiency of resource use. The method used in this study is a literature review, which analyzes various relevant literature on performance-based budgeting in local governments. From this analysis, it was found that although this system increases effectiveness and economy, changes in public management and strengthening organizational capacity are still needed to achieve optimal efficiency. The results of this study are expected to provide insight into the importance of careful planning, disciplined implementation, and transparent evaluation in improving local financial management and improving overall local government performance.